Management of Islamic Education on Construction of Early Childhood Curriculum - Elyana, Luluk; Das, Rajib Kumar (Universitas Negeri Semarang, 2022)
This article describes the management of Islamic education in the construction of early childhood education curriculum at Annida Ya Fatimah school, Jepat Lor village, Tayu Pati. By using a qualitative research approach, the researchers found that the curriculum at Annida ya Fatimah school builds the construction of Islamic education, local wisdom and Islamic culture of the local community. This construction is realized through integration into curriculum development and learning practices. This construction implements Islamic education based on the the peculiar local wisdom as an effort to preserve Islamic culture on the north coast of Java. The orientation of the curriculum construction is relevant to Annida Ya Fatimah's school, which indeed shows that Early Childhood Education Institutions have a tradition of local wisdom in coastal areas. This study shows that schools play a major role in preserving the unique traditions, local wisdom and Islamic culture of the local community by integrating them into curriculum construction and learning as the implementation of Islamic education at public schools. The integration of Islamic culture into curriculum construction and daily learning practices is manifested in early childhood education service programs. Early childhood education services at the Annida Ya Fatimah school focus on shaping attitudes and developing the character of the Islamic generation, as well as providing consistency in Islamic attitudes to continue to the next level of education.